Peningkatan Hasil Belajar dan Aktivitas Belajar Siswa Melalui Model Pembelajaran Tutor Sebaya - Suhartati, Tri; Arianto, Tatok (JURNAL PENA EDUKASI, 2022)
The research was purpose to increase the learning achievement and learning activities of students in class XI IPS-2 SMA Kristen Immanuel Batam through peer teaching learning model. This research was conducted in the academic year 2019/2020 even semester and the research participants were 24 students. The study was cconducted in February until June 2020. The data collection technique was from primary data on learning achievement and student learning activity questionnaires. Qalitative descriptive data analysis technique. The results of this study have increased student learning achievement and learning activities after using the peer teaching learning model. The pre-cycle learning achievement completeness score was 4.67%, and the pre-cycle average score was 61.46. The score of completeness learning achievement in cycle I is 79.17%, and the average score of cycle I is 76.25. The score of completenees of learning achievement in cycle II is 91.67%, and the average score of cycle II is 83.96. The precentage of pre-cycle high category learning activities was 33.33%. The percentage of learning activities in the high category of cycle I was 70.83%. The percentage of learning activities in the high category of cycle II was 87.50%.